New Florida Foliage Plant Cultivar: Dieffenbachia 'Sparkles' - Richard J. Henny; Jianjun Chen; Terri A. Mellich (EDIS, 2010)
ENH1173, a 4-page illustrated fact sheet by R. J. Henny, J. Chen, and T. A. Mellich, describes the origin, description, and availability of this commercial foliage cultivar characterized by it's bright leaf color and attractive paisley mottled appearance. Includes additional sources of information. Published by the UF Department of Environmental Horticulture, September 2010.